A Comparison of Histomorphometric Data Collection Methods*. Issue 1 (23rd May 2012) - Stewart, Marissa C.; McCormick, Lara E.; Goliath, Jesse R.; Sciulli, Paul W.; Stout, Sam D.
<x xml:space="preserve">Abstract</x> Abstract: Although many variables that skeletal biologists examine have been standardized, the actual techniques used to collect these data from bone thin sections vary. This project compares different methods of obtaining data (relative cortical area values) for histomorphometric research. One visual and three digital methods of histomorphometric data collection are compared: (i) Merz microscopic eyepiece counting reticule, (ii) flatbed scanner, (iii) overlaying multiple images of a thin section, and (iv) digital SLR camera with macro settings. The discussion includes a comparison of usability factors such as cost, time, user‐experience, and ease‐of‐use, which vary for each method. Values from the different methods are compared using ANOVA tests to evaluate inter‐method, inter‐observer, and intra‐observer variability. Intra‐observer error was greater for the microscopic method, although the error values are concomitant with experience. We found no statistically significant differences between the four methods examined, but certain caveats must be addressed when these methods are used.